Protecting Copper Oxidation State via Intermediate Confinement for Selective CO2 Electroreduction to C2+ Fuels - Yang, Peng-Peng; Zhang, Xiao-Long; Gao, Fei-Yue; Zheng, Ya-Rong; Niu, Zhuang-Zhuang; Yu, Xingxing; Liu, Ren; Wu, Zhi-Zheng; Qin, Shuai; Chi, Li-Ping; Duan, Yu; Ma, Tao; et al. (Journal of the American Chemical Society, 2020)
Selective and efficient catalytic conversion of carbon dioxide (CO2) into value-added fuels and feedstocks provides an ideal avenue to high-density renewable energy storage. An impediment to enabling deep CO2 reduction to oxygenates and hydrocarbons (e.g., C2+ compounds) is the difficulty of coupling carbon–carbon bonds efficiently. Copper in the +1 oxidation state has been thought to be active for catalyzing C2+ formation, whereas it is prone to being reduced to Cu0 at cathodic potentials. Here we report that catalysts with nanocavities can confine carbon intermediates formed in situ, which in turn covers the local catalyst surface and thereby stabilizes Cu+ species. Experimental measurements on multihollow cuprous oxide catalyst exhibit a C2+ Faradaic efficiency of 75.2 ± 2.7% at a C2+ partial current density of 267 ± 13 mA cm–2 and a large C2+-to-C1 ratio of ∼7.2. Operando Raman spectra, in conjunction with X-ray absorption studies, confirm that Cu+ species in the as-designed catalyst are well retained during CO2 reduction, which leads to the marked C2+ selectivity at a large conversion rate.